Developing a Gender-sensitive Digital Trade Regulatory Framework in the Promotion of Women in E-commerce : A Malawian Perspective - Masamba, Magalie (University of Pretoria, 2023)
Mini Dissertation (LLM (International Trade and Investment Law in Africa))--University of Pretoria, 2023.